Fatores associados ao trauma mamilar na maternidade Factors associated with nipple trauma in the maternity unit - Kelly Pereira Coca; Mônica Antar Gamba; Rebeca de Souza e Silva; Ana Cristina F. V. Abrão (Elsevier, 2009)
OBJETIVO: Identificar os fatores associados ao trauma mamilar em mulheres em aleitamento materno exclusivo na maternidade. MÉTODOS: Estudo caso-controle com 146 puérperas internadas nas enfermarias de alojamento conjunto, sendo 73 casos, definidos como mulheres com trauma mamilar, e 73 controles, definidos como ausência da patologia. Diariamente buscaram-se mulheres em aleitamento materno exclusivo com diagnóstico de lesão mamilar, identificada por meio de lupa. Foram estudadas variáveis sociodemográficas, obstétricas e neonatais. Na análise estatística, utilizou-se modelo de regressão logística. RESULTADOS: Casos e controles mostraram-se semelhantes quanto às variáveis sociodemográficas, embora a ausência do companheiro tenha sido mais frequente no grupo de mulheres com trauma mamilar. As variáveis primiparidade (OR 3,16; IC95% 1,19-8,42), ausência do companheiro (OR 3,25; IC95% 1,18-8,93), mama túrgida e/ou ingurgitada (OR 12,31; IC95% 4,48-33,78), mamilo semiprotruso e/ou malformado (OR 4,69; IC95% 1,50-14,62) e despigmentação dos mamilos (OR 13,98; IC95% 4,43-44,06) comportaram-se como fatores associados ao trauma mamilar. CONCLUSÃO: Primiparidade, ausência do companheiro, mamas túrgidas e ingurgitadas, mamilos semiprotrusos e/ou malformados e despigmentados estão associados ao trauma mamilar. OBJECTIVE: To identify factors associated with nipple trauma in women breastfeeding exclusively in a maternity unit. METHODS: This was a case-control study that recruited 146 recently-delivered mothers in rooming-in wards: 73 cases, defined as women with nipple trauma, and 73 controls, defined as women free from this pathology. Women breastfeeding exclusively were tested daily for a diagnosis of nipple injury, identified using a magnifying glass. Sociodemographic, obstetric and neonatal variables were studied. A logistic regression model was used for statistical analysis. RESULTS: Cases and controls proved to be comparable in terms of their sociodemographic variables, although the women with nipple trauma were more likely not to be living with a partner. The following variables were found to be factors associated with nipple trauma: primiparity (OR 3.16; 95%CI 1.19-8.42), not living with a partner (OR 3.25; 95%CI 1.18-8.93), turgid and/or engorged breasts (OR 12.31; 95%CI 4.48-33.78), semi-protruding and/or malformed nipples (OR 4.69; 95%CI 1.50-14.62), and depigmentation of nipples (OR 13.98; 95%CI 4.43-44.06). CONCLUSION: Primiparity, not living with a partner, turgid and/or engorged breasts, semi-protruding and/or malformed nipples, and depigmentated nipples are associated with nipple trauma.